ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA HOTEL ARISTA PALEMBANG - Afrizawati Afrizawati (Politeknik Negeri Sriwijaya, 2012)
The Quality of service is a benchmark to known good or not a service, because the quality of service will affect directly or indirectly the level of customer satisfaction whether it will have an impact on customer loyalty. To determine the extent effect quality of service on customer satisfaction at Arista Hotel Palembang and which one the dominant variables affecting the customer satisfaction, the results showing the dominant variable that influence customer satisfaction is physical evidence, with the variable regression coefficient of 0.000 and the regression results indicate show 40.27 percent of certain service quality provided by the Arista Hotel Palembang that affect customer satisfaction Arista hotel Palembang. Mean while the other of variables are variable assurance and empathy showing significant levels of 0.040 and 0.008, and than variables reliability and responsiveness are not significantly influence customer satisfaction. So it can be conclusion based on that customer satisfaction, which is the physical evidence variable that significantly impact the quality of service at Arista Hotel Palembang.